Hubungan Pengetahuan Ibu Tentang Gizi Balita Dengan Pertumbuhan Berat Badan Balita Pada KMS di Posyandu Dusun Banggel Desa Jebeng Kecamatan Slahung Kabupaten Ponorogo. - eliya rohmah; muniati murniati; Binti Nurdianasari (Jurnal Delima Harapan, 2018)
The growth of toddlers can be known if each month weighed. Weighing results arerecorded in KMS, and between the KMS weight point of last month's weighing results andthe month's weighing results are attributed to a line. Based on the results of preliminarystudy on 7 mothers found out the results of two primary school graduates, 2 mothers ofjunior high school, and 3 mothers of high school graduates. Then the mother was askedabout the nutrition of toddlers aged 1-5 years and 4 mothers know but do not understandthe whole while 3 mothers do not know at all about nutrition balita1-5 years, from 7mother toddler 3 balitanya experience weight gain while 4 balita weight drop .This study aims to determine the relationship of mother's knowledge about the nutrition ofchildren under five with weight growth of children under five. The design of this researchis analytical method with Cross Sectional approach. With the total population of 61respondents, the sample of the research is 31 respondents using sampling technique thatis accidental sampling. Data collection was obtained by questionnaire and view of KMS.Data were analyzed using spearman rank.The result of the research shows that from 31 respondents, most of BB did not increasewith 19 respondents (61,3%) and almost half of them were less knowledge with 14respondents (45,2%). Statistical test using spearman rankdidapatkan ρ = 0.000 withsignificance level ρ <0,05 then Ho is rejected which means there is relationship of motherknowledge about nutrition of balita with growth of BB and level of closeness strongrelation.Based on the results of the study is expected health workers, especially midwives toimprove the role and function of services for the community in providing healthinformation, especially about the importance of weight growth in toddlers.